An ion channel of the degenerin/epithelial sodium channel superfamily controls the defecation rhythm in Caenorhabditis elegans - Take-uchi, Masaya (National Academy of Sciences, 1998)
Ultradian rhythms are widespread phenomena found in various biological organisms. A typical example is the defecation behavior of the nematode Caenorhabditis elegans, which repeats at about 45-sec intervals. To elucidate the mechanism, we studied flr-1 mutants, which show very short defecation cycle periods. The mutations also affect some food-related functions, including growth rate, the expulsion step of defecation behavior, and the regulation of the dauer larva (a nonfeeding, special third-stage larva) formation in the unc-3 (Olf-1/EBF homolog) background. The flr-1 gene encodes a novel ion channel belonging to the DEG/ENaC (C. elegans degenerin and mammalian epithelial sodium channel) superfamily. A flr-1∷GFP (green fluorescent protein) fusion gene that can rescue the flr-1 mutant phenotypes is expressed only in the intestine from embryos to adults. These results suggest that FLR-1 may be a component of an intestinal regulatory system that controls the defecation rhythm as well as other functions.